THE KINEMATIC OF RELATIVISTIC MOTIONS IN ASTROPHYSICAL OBJECTS - KEY TO THE VERIFICATION OF THE TIME - COORDINATE TRANSFORMATIONS - Larionov, M. G. (Одеські астрономічні публікації, 2017)
On the basis of the independent interpretation of Mickelson-Morley experiment the not Lorenz transformations were suggested. Astrophysical data on kinematic for relativistic out flows in galactic sources was investigated. It was shown that the differences between standard relativistic transformations and the suggested ones occur at the v3/c3 power. That does not allow to accept or to reject this or that kind of transformations. Peculiarities of the observational data being the result of suggested transformations were enumerated.